Pelaksanaan Sanitasi Total Berbasis Masyarakat - Radhuha Ekinaro (Jurnal El-Thawalib, 2022)
Community Based Total Sanitation is a policy issued by the government to change hygiene and sanitation behavior through community empowerment to maintain cleanliness in public places such as mosques. However, several mosques in the Southeast Padangsidimpuan District have no bathroom facilities equipped with a septic tank. these risks can reduce the quality of life, buildings and the environment due to low access to services in the sanitation sector. From these problems, the authors want to know how the implementation of the Regulation of the Minister of Health of the Republic of Indonesia no. 3 of 2014 Article 4 Paragraph (1) concerning Community-Based Total Sanitation at the Mosque of Southeast Padangsidimpuan District, what are the factors that hinder the implementation of the Regulation of the Minister of Health of the Republic of Indonesia No. 3 of 2014 Article 4 Paragraph (1) concerning Community-Based Total Sanitation, and How is Fiqh Siyasah Review of the Implementation of the Regulation of the Minister of Health of the Republic of Indonesia No. 3 of 2014 Article 4 Paragraph (1). The type of research used in this research is field research, using qualitative descriptive analysis methods, namely describing phenomena or events that occur in the field. The data collection instruments used consisted of interviews, observations, and documentation. The results of this study state that there are 3 stages of implementing the Regulation of the Minister of Health of the Republic of Indonesia No. 3 of 2014 Article 4 Paragraph 1 concerning Community-Based Total Sanitation (Study at the Mosque of Southeast Padangsidimpuan District) namely the preparation stage, triggering stage and monitoring stage. The factors that support its implementation are caused by factors, education level factors, income factors and factors behavior, and if it is seen from the Siyasah Fiqh Review that the government regulations regarding standard sanitation for the manufacture of septic tanks can be seen from the side of Siyasah Duturiyah discussing government policies and regulations.